1978
DOI: 10.1212/wnl.28.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Huntington chorea

Abstract: A brain biopsy from a 20-year-old patient whose clinical course was marked by progressive dementia and chorea since age 10 years showed increased amounts of lipofuscin, abnormal mitochondria, and other organelles in cortical neurons, neurites, and astrocytes. Juvenile Huntington chorea was confirmed at autopsy. High levels of three histone-like proteins (molecular weight 10,000 to 16,000) in the microsomal fraction of purified neurons were found by SDS-polyacrylamide gel electrophoresis. Fatty acids were abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 0 publications
3
40
1
1
Order By: Relevance
“…Fatty acid composition of SM from human cerebral white matter was reported to be abnormal in patients with juvenile and adult HD, with a shift toward shorter chain fatty acid. However, this event does not seem to be specific for this disease, but rather an index of disturbed myelination and demyelination, since it has been associated with an immature myelin and detected also in young children and in several cases of non-specific brain damage associated with demyelination [276,277]. On the other hand, changes in the GSL composition have been observed in erythrocytes from HD patients [278], and a marked reduction in the ganglioside concentration was detected in the striatum of HD human brains and in rat brains after lesioning by intrastriatal injection of kainic acid [279].…”
Section: Huntington's Diseasementioning
confidence: 94%
“…Fatty acid composition of SM from human cerebral white matter was reported to be abnormal in patients with juvenile and adult HD, with a shift toward shorter chain fatty acid. However, this event does not seem to be specific for this disease, but rather an index of disturbed myelination and demyelination, since it has been associated with an immature myelin and detected also in young children and in several cases of non-specific brain damage associated with demyelination [276,277]. On the other hand, changes in the GSL composition have been observed in erythrocytes from HD patients [278], and a marked reduction in the ganglioside concentration was detected in the striatum of HD human brains and in rat brains after lesioning by intrastriatal injection of kainic acid [279].…”
Section: Huntington's Diseasementioning
confidence: 94%
“…In platelets, one study reported decreased complex I activity and no change in the activities of complexes II-III and IV (Parker et al 1990a). Also ultrastructural abnormalities in mitochondria have been described in HD cortical tissue (Goebel et al 1978;Gardian and Vecsei 2004).…”
Section: Mitochondrial Involvement In Huntington's Diseasementioning
confidence: 99%
“…The principal indicator of an energetic involvement in the disease process is the observation of insidious weight loss in Huntington's disease patients despite a sustained caloric intake (O'Brien et al, 1990). Subsequently, positron emission tomography (PET) and biochemical studies in postmortem brain have shown selective metabolic defects in brain regions targeted by the disease, and mitochondrial abnormalities in Huntington's disease have been identified in ultrastructural studies of cortical biopsies from juvenile and adult-onset Huntington's disease cases (Goebel et al, 1978).…”
Section: A Bioenergetic Defectsmentioning
confidence: 99%